2010
DOI: 10.1002/jssc.200900620
|View full text |Cite
|
Sign up to set email alerts
|

Rapid identification and preparative isolation of antioxidant components in licorice

Abstract: This study employed the online HPLC-2,2'-azinobis-(3-ethylbenzothiazoline-6-sulfonate radical cation (ABTS(+*)) bioassay to rapidly determine antioxidant compounds occurring in the licorice extract of Glycyrrhiza uralensis. The negative peaks of the ABTS(+*) radical scavenging detection system, which indicated the presence of antioxidant activity, were monitored by measuring the decrease in absorbance at 734 nm. The ABTS(+)-based antioxidant activity profile showed that three peaks exhibited antioxidant activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In addition, it was found that HEGU reduces then umbers of viable HT-29 human colon, MDA-MB-231 human breast, and DU145 human prostate cancer cells [12]. Licorice root contains triterpenesaponins, flavonoids, isoflavonoids and chalcones, coumarins, stilbenoids, as well as miscellaneous compounds as biologically active components [15,35]. Recently, Lee and colleagues attempted to isolate antioxidant compounds from licorice using ABTS assay and identified DGC, DGD, and IsoA as major antioxidants [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it was found that HEGU reduces then umbers of viable HT-29 human colon, MDA-MB-231 human breast, and DU145 human prostate cancer cells [12]. Licorice root contains triterpenesaponins, flavonoids, isoflavonoids and chalcones, coumarins, stilbenoids, as well as miscellaneous compounds as biologically active components [15,35]. Recently, Lee and colleagues attempted to isolate antioxidant compounds from licorice using ABTS assay and identified DGC, DGD, and IsoA as major antioxidants [15].…”
Section: Discussionmentioning
confidence: 99%
“…Licorice root contains triterpenesaponins, flavonoids, isoflavonoids and chalcones, coumarins, stilbenoids, as well as miscellaneous compounds as biologically active components [15,35]. Recently, Lee and colleagues attempted to isolate antioxidant compounds from licorice using ABTS assay and identified DGC, DGD, and IsoA as major antioxidants [15]. However, the antioxidant activities of these three compounds have not been comparatively studied until now.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those fractions were purified by preparative TLC on silica gel or by preparative HPLC to give isolicoflavonol (7) [22], isoglycycoumarin (8) [23], licoarylcoumarin (9) [24], formononetin (10) [25], and 6"-O-acetylliquiritin (11) [26]. On the other hand, the remaining part of the ethyl acetate fraction was directly subjected to column chromatography on ODS-gel, and fractions from the column were further purified by column chromatography on MCI-gel CHP-20P, and by preparative HPLC or preparative TLC, to give liquiritin (12) [27], p-hydroxybenzoic acid (13), semilicoisoflavone B (14) [28], glycyrol (15) [29], glycyrin (16) [29], gancaonin I (17) [30], isoglycyrol (18) [31], liquiritigenin (19) [27], gancaonin G (20) [36], glicoricone (25) [37], glycycoumarin (26) [38], licocoumarone (27) [29], licoricone (28) [39], glyasperin D (29) [40], isoangustone A (30) [41], and two additional compounds temporarily named compounds A (31), and B (32). Since several phenolics from licorice display potent antibacterial effects against methicillin-resistant Staphylococcus aureus (MRSA), and also show suppressing effects on the oxacillin resistance of MRSA, as we have reported previously [11], we have also investigated the effect of these licorice phenolics on VRE.…”
Section: Resultsmentioning
confidence: 99%
“…Two-phase solvent systems were tested by changing the volume of the solvent to obtain the optimum composition to yield suitable partition coefficient ( K values). The K values were determined as described [ 19 ]. Briefly, the composition of a two-phase solvent system was selected according to the K of the target compounds of crude extract.…”
Section: Methodsmentioning
confidence: 99%